IMF Staff papers : Volume 9 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1962)
This paper provides an analysis of attempts at international coordination of national policies leads to the conclusion that true international action that has a good chance to succeed for specific measures, such as changes in exchange rates, customs tariffs, and perhaps discount rates. There is, on the other hand, little reason to assume that the desire prevalent in all countries for full employment, stable prices, and growth could be supported to any important degree by the acceptance of international obligations. The targets of economic policy as they have been put forward for our discussion appear simple and noncontroversial: reasonable price stability, full employment and an adequate rate of growth, and balance of payments equilibrium. If in any country the relationship between wages and employment is such that at full employment wages increase more rapidly than is compatible with price stability, then obviously the price and employment objectives of that country are not compatible.